2005
DOI: 10.1172/jci200523025
|View full text |Cite
|
Sign up to set email alerts
|

Human lupus autoantibody–DNA complexes activate DCs through cooperation of CD32 and TLR9

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by pathogenic autoantibodies against nucleoproteins and DNA. Here we show that DNA-containing immune complexes (ICs) within lupus serum (SLE-ICs), but not protein-containing ICs from other autoimmune rheumatic diseases, stimulates plasmacytoid DCs (PDCs) to produce cytokines and chemokines via a cooperative interaction between Toll-like receptor 9 (TLR9) and FcγRIIa (CD32). SLE-ICs transiently colocalized to a subcellular compartment con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
334
2
10

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 317 publications
(355 citation statements)
references
References 52 publications
9
334
2
10
Order By: Relevance
“…The ongoing production of IFN␣ in many patients with SLE suggests the presence of inducers that trigger expression of IFN␣ genes. Therefore, an important finding was that DNA-containing immune complexes in patients with SLE can induce IFN␣ production by NIPCs/PDCs, and that the occurrence of such interferogenic immune complexes is associated with active disease (5,6,70). When formed, these immune complexes are internalized via Fc␥RIIa and reach the endosomes of NIPCs/PDCs, with subsequent activation of the relevant TLR and induction of IFN␣/␤ production (20,70).…”
Section: Activation and Regulation Of Nipcs/pdcs In Slementioning
confidence: 99%
“…The ongoing production of IFN␣ in many patients with SLE suggests the presence of inducers that trigger expression of IFN␣ genes. Therefore, an important finding was that DNA-containing immune complexes in patients with SLE can induce IFN␣ production by NIPCs/PDCs, and that the occurrence of such interferogenic immune complexes is associated with active disease (5,6,70). When formed, these immune complexes are internalized via Fc␥RIIa and reach the endosomes of NIPCs/PDCs, with subsequent activation of the relevant TLR and induction of IFN␣/␤ production (20,70).…”
Section: Activation and Regulation Of Nipcs/pdcs In Slementioning
confidence: 99%
“…Its recognition of CpG nucleotide sequences appears to enhance the activation of B cells via the B cell receptor (1)(2)(3). Subsequent studies in humans have shown that dendritic cells are activated by chromatin immune complexes and that this effect is mediated by a cooperation between TLR-9 and Fc␥ receptors (4,5). These observations suggest that genetic variation affecting the costimulatory function of TLR-9 could lead to differences in B cell response to autoantigens and dendritic cell response to chromatin immune complexes.…”
mentioning
confidence: 99%
“…However, it is well known that both IFNa and TNFa are over-expressed in many patients with SLE and other autoimmune diseases, sometimes associated with disease activity [40,41]. In such patients, the presence of nucleic acid-containing immune-complexes induces plasmacytoid DCs, and probably other cell types, to produce IFNa [42] after stimulation across TLR-7/9 [9,43]. Similarly, immune-complexes can induce TNFa production [44].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hydroxychloroquine blocks TLR-mediated activation of pDC in vitro, as shown by inhibition of IFNa synthesis, either after induction by immune-complexes [9] or upon stimulation with TLR9 agonists [48,49]. Recently, it has been observed that the significant clinical improvement in SLE patients after hydroxychloroquine therapy correlated with reductions in IFNa levels [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation